2015
DOI: 10.1038/nature14964
|View full text |Cite
|
Sign up to set email alerts
|

Conventional superconductivity at 203 kelvin at high pressures in the sulfur hydride system

Abstract: A superconductor is a material that can conduct electricity with no resistance below its critical temperature (T c ). The highest T c that has been achieved in cuprates 1 is 133 K at ambient pressure 2 and 164 K at high pressures 3 . As the nature of superconductivity in these materials has still not been explained, the prospects for a higher T c are not clear. In contrast, the BardeenCooper-Schrieffer (BCS) theory gives a guide for achieving high T c and does not put bounds on T c , all that is needed is a fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

112
2,056
8
14

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,285 publications
(2,190 citation statements)
references
References 29 publications
112
2,056
8
14
Order By: Relevance
“…Such rethinking has far reaching implications for phonon interactions with other quantum particles such as neutrons, electrons and photons, since the momentum associated with diffusons and locons is unclear. [41][42][43][44][45][46][47][48][49] Furthermore, the results herein have shown that phonons cannot in general be thought of exclusively as plane waves. Instead, we believe a more general perspective is to classify phonons according to the three groups identified by Allen and Feldman, 10 and more generally think of a phonon as "a quanta of normal mode vibrational energy".…”
Section: Resultsmentioning
confidence: 63%
“…Such rethinking has far reaching implications for phonon interactions with other quantum particles such as neutrons, electrons and photons, since the momentum associated with diffusons and locons is unclear. [41][42][43][44][45][46][47][48][49] Furthermore, the results herein have shown that phonons cannot in general be thought of exclusively as plane waves. Instead, we believe a more general perspective is to classify phonons according to the three groups identified by Allen and Feldman, 10 and more generally think of a phonon as "a quanta of normal mode vibrational energy".…”
Section: Resultsmentioning
confidence: 63%
“…The current state of the art for the highesttemperature zero-resistance superconducting state is around 153 K for Hg-based cuprate superconductors under high pressures above 10 GPa (refs 8,9), and around 190 K for H 3 S under a very high pressure of 200 GPa (ref. 10). As for the present status of applications of high-temperature superconductors, benchmark examination towards large-scale application are in progress.…”
Section: Mottronicsmentioning
confidence: 99%
“…The newly discovered stable phases magnesium and iron peroxides (MgO 2 and FeO 2 ) formed from a high pressure and temperature redox reaction provide a new look at oxygen and hydrogen cycling in the deep earth interior 17, 18. Ultrahigh pressure sulfur hydride demonstrates superconducting behavior at record high temperature, 203 K 19. We addressed two questions.…”
Section: Introductionmentioning
confidence: 99%